Formulation and phase behavior study of a nonionic triglyceride microemulsion to increase hydrocarbon production - Jeirani, Z.; Mohamed Jan, B.; Si Ali, B.; Noor, I.M.; See, C.H.; Saphanuchart, W. (Elsevier, 2013)
It is no secret that during microemulsion flooding, the oil entrapped in rock pores can be easily removed when a new Winsor Type III microemulsion is formed in situ. Formulation of an efficient microemulsion in tertiary oil recovery requires good understanding of its phase behavior. This paper presents the phase behavior study of a triglyceride microemulsion before and after n-octane solubilization in formulating an efficient triglyceride microemulsion. The effects of solubilized oil as co-oil, salinity, surfactant concentration and co-surfactant concentration on the phase behavior of a triglyceride microemulsion were investigated. The optimized aqueous phase composition of the triglyceride microemulsion was adjusted at 1 wt% alkyl polyglycosides, 3 wt% glyceryl monooleate, 3 wt% sodium chloride, and 93 wt% de-ionized water. It is concluded that this condition represents the widest range and the maximum volume of Winsor Type III microemulsion that can be achieved for the triglyceride microemulsion after fluid injection.